2011
DOI: 10.1021/np100638h
|View full text |Cite
|
Sign up to set email alerts
|

Natural Compound Cudraflavone B Shows Promising Anti-inflammatory Properties in Vitro

Abstract: Cudraflavone B (1) is a prenylated flavonoid found in large amounts in the roots of Morus alba, a plant used as a herbal remedy for its reputed anti-inflammatory properties. The present study shows that this compound causes a significant inhibition of inflammatory mediators in selected in vitro models. Thus, 1 was identified as a potent inhibitor of tumor necrosis factor α (TNFα) gene expression and secretion by blocking the translocation of nuclear factor κB (NF-κB) from the cytoplasm to the nucleus in macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 33 publications
2
44
1
1
Order By: Relevance
“…It was a powerful TNF-a inhibitor by preventing the NF-kB translocation from the cytoplasm to the nucleus. The NF-Kb inhibition activity leads to an inhibition in the gene expressions of COX-2 [40,41]. Resveratrol purified from MA inhibits a secretion of IL-8 by blocking phosphorylation of MAPK and activation of NF-kappa B in LPSinduced human monocytic cell line THP-1 [38,42].…”
Section: Discussionmentioning
confidence: 99%
“…It was a powerful TNF-a inhibitor by preventing the NF-kB translocation from the cytoplasm to the nucleus. The NF-Kb inhibition activity leads to an inhibition in the gene expressions of COX-2 [40,41]. Resveratrol purified from MA inhibits a secretion of IL-8 by blocking phosphorylation of MAPK and activation of NF-kappa B in LPSinduced human monocytic cell line THP-1 [38,42].…”
Section: Discussionmentioning
confidence: 99%
“…Eriodictyol (24) and naringenin (25) were used as non-prenylated flavanones for anti-inflammatory potential testing and were obtained from Sigma-Aldrich, with declared purity exceeding 95%.…”
Section: Journal Of Natural Productsmentioning
confidence: 99%
“…Its molecular formula was determined by HRESIMS to be C 25 , 441.1913). The signals of oxygen-bearing carbons (δ C 72.3 and 77.5) were again present, but the observed HMBC correlations indicated that oxidation took place in a different part of the chain than in compounds 1−3.…”
mentioning
confidence: 99%
See 2 more Smart Citations